(8u³ + 8u² + 6) + (4u³<span> - 6u + 3) =
</span>8u³ + 8u² + 6 + 4u³ - 6u + 3 =
12u³ + 8u² - 6u + 9
Answer:
x = -2
And, x = 7 ÷ 2
Step-by-step explanation:
Given that
y = 2x^2
y = 3x + 14
Now equate these two above equations
2x^2 = 3x + 14
2x^2 - 3x - 14
2x^2 -7x + 4x - 14
x(2x - 7) + 2(2x - 7)
(x + 2) (2x - 7)
So it can be x = -2
And, x = 7 ÷ 2
Answer:
5,6241
Step-by-step explanation:
I have no idea if this is correct but I hope it is. I hope this helps.
Answer:
if you're talking about slope intercept then
y= 8/5x + 11/5